The Effects of Retro-Themed Content, Emotional Resonance, and Brand Consistency on Customer Re-Engagement - Wijayanto, Gatot; Purwoko, Bambang (IJBLE Scientific Publications Community Inc., 2025)
This study investigates the effects of retro-themed content, emotional resonance, and brand consistency on customer re-engagement. Using a structured questionnaire adapted from established scales, data were collected from 300 respondents and analyzed through descriptive statistics, reliability testing, confirmatory factor analysis, and multiple regression. The findings reveal that retro-themed content positively influences customer re-engagement both directly and indirectly through emotional resonance, which serves as a significant mediator. Brand consistency also contributes positively to customer re-engagement, though to a lesser extent. These results highlight the importance of leveraging nostalgia in marketing strategies while ensuring consistent brand messaging to strengthen emotional connections and encourage repeated interactions. The study provides theoretical and practical insights for marketers seeking to enhance customer loyalty through retro-themed campaigns.